2014
DOI: 10.1080/19443994.2014.959735
|View full text |Cite
|
Sign up to set email alerts
|

CFD prediction of scalar transport in thin channels for reverse electrodialysis

Abstract: Abstract. Reverse ElectroDialysis (RED) is a very promising technology allowing the electrochemical potential difference of a salinity gradient to be directly converted into electric energy. The fluid dynamics optimization of the thin channels used in RED is still an open problem.The present preliminary work focuses on the Computational Fluid Dynamics (CFD) simulation of the flow and concentration fields in these channels. In particular three different configurations were investigated: a channel unprovided wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Several CFD studies of spacer-filled channels based on the above Unit Cell approach can be found in the literature [2,35,[37][38][39][40][41][65][66][67][68]. This treatment is justified by the fact that the fully developed fields are attained after just a few Unit Cells [36,42].…”
Section: Computational Domain and Boundary Conditionsmentioning
confidence: 98%
“…Several CFD studies of spacer-filled channels based on the above Unit Cell approach can be found in the literature [2,35,[37][38][39][40][41][65][66][67][68]. This treatment is justified by the fact that the fully developed fields are attained after just a few Unit Cells [36,42].…”
Section: Computational Domain and Boundary Conditionsmentioning
confidence: 98%
“…Many CFD studies can be found in the literature on spacer-filled channels [2,[42][43][44][45][46][47] and corrugated channels [30,31,33,35] based on this approach, because the fully developed flow condition is attained after just a few unit cells [48].…”
Section: Computational Domains and Boundary Conditionsmentioning
confidence: 99%
“…It results into grids with a number of computational cells ranging from ~1·10 6 to ~4·10 6 depending on the specific pitch to height ratio. A hybrid hexahedral-tetrahedral grid was generated for the case of the spacer-filled channel (~1.6·10 6 of computational cells) as described in detail elsewhere [2,42,47]. Figure 5 shows enlarged details of meshes employed for two profiled-membrane channels and for the spacer-filled channel.…”
Section: Computational Domains and Boundary Conditionsmentioning
confidence: 99%
“…On the other hand, even at very low Reynolds numbers, the flow patterns in these channels may be very complex and characterized by very small structures, thus requiring very fine meshes to be properly simulated. The Unit Cell approach is the generally adopted solution to reliably simulate these channels [19,30,31,[33][34][35]39,41,42,[48][49][50]. The Unit Cell represents the repeating unit of the whole periodic domain which is typically investigated in CFD studies.…”
Section: Unit Cell Approachmentioning
confidence: 99%
“…Only few works have been devoted to the CFD simulation in the low Reynolds numbers range typical for RED. Beyond the works of our research group [19,[39][40][41][42], the only example is the work of Pawlowski et al [43].…”
Section: Introductionmentioning
confidence: 99%